Future-scaping: lessons learned from co-visioning a resilient future within an integrated landscape and seascape approach (ILSA) in eastern coastal Taiwan - Karim, Paulina G.; Lee, Kuang-Chung (Frontiers in Sustainable Food Systems, 2025)
This study addresses knowledge gaps in long-term integrated landscape and seascape approaches (ILSA) by examining the facilitation of future-scaping—a participatory method for co-visioning futures and setting actionable goals—in the Xinshe “Forest–River–Farmlands–Ocean” Eco-Agriculture Initiative in eastern coastal Taiwan. Drawing on facilitator perspectives since 2016, we show how future-scaping tools helped the Dipit and pateRungan Indigenous tribes, government agencies, and the local school articulate 2026 and 2050 visions and translate them into 19 priority objectives. The process revealed shared aspirations for ecological integrity, sustainable agriculture, cultural revival, youth return, and equitable governance; fostered inclusive knowledge weaving; and enabled adaptive shifts in the initiative’s concluding phase. Lessons learned are discussed through the Problems, People, and Process dimensions of the Xinshe ILSA’s 5P + S model, emphasizing structured flexibility to bridge aspiration–implementation gaps, sustained inclusivity across knowledge systems, and facilitation as a key boundary function. As a model for rural transformation, the Xinshe ILSA affirms co-produced, iterative approaches as vital for navigating nexus challenges and advancing toward living in harmony with nature.